Craniofacial Fibrous Dysplasiaa Rare Case Report in a Tertiary Eye Hospital (Journal of National Institute of Ophthalmology, 2022)
Purpose: Fibrous dysplasia (FD) is a rare fibro-osseous lesion of the osseous structures of the body. Craniofacial FD confined to contiguous bones of the craniofacial skeleton. Purpose of the study is to report such a rare case which was diagnosed and managed in the outpatient department in our tertiary eye hospital.Method: A 12-year-old girl complaint of painless swelling over right side of eyebrow for 4 months.Facial examination revealed well-defined bony swelling rounded in shape with hard consistency, nontender; diameter 10x10 mm; overlying skin free; no regional lymphadenopathy. Visual acuity was 6/6. Anterior and posterior segment revealed normal. Ocular motility was full. No other swelling was present in body and café-au-lait spots were absent. Routine investigations such as hemogram, serum calcium and serum alkaline phosphatase (ALP) were performed. Among them ALP was raised to 300 U/L. CT scan showed a radio dense mass with ground-glass appearance involving right frontal bone whose expansion causing facial asymmetry .An incisional biopsy with histopathological analysis was done. It showed irregular bony trabeculae in chinese script pattern scattered within fibrous stroma. The bone appeared woven rather than lamellar. MRI suggest diffuse thickening of right frontal bone.Result: Clinical history, radiographic assessment and histological features suggested that it was a case of craniofacial FD involving right side of frontal bone.Conclusion: Detection of early suspicious sign for diagnosis and early initiation for management is crucial to prevent the long-term complication with avert the process of optic nerve compression.J. Natl. Inst. Ophthalmol. 2022;5(1):46-50